2021
DOI: 10.1111/edt.12676
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Dentists’ management of permanent dentition traumatic dental injuries in 7‐ to 16‐year‐olds: A sequential mixed‐methods study

Abstract: Background/Aims Primary care dentists play a pivotal role in the management of traumatic dental injuries in children, despite little evidence on the barriers they face in providing care. The aim of this study was to explore and contextualize the knowledge and attitudes of general dental practitioners regarding their management of permanent dentition traumatic dental injuries in children aged 7–16 years old. Material and Methods A two‐phase sequential mixed‐methods study included a questionnaire that was dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
2
6
0
1
Order By: Relevance
“…Ultimately, it may only truly be successful if recording the MDS‐TDI defined outcomes act as a driver for payment. A lack of sufficient financial remuneration associated with the long‐term management of dental trauma was the main barrier for dentists to manage TDI in primary care 29 . This has long been identified as an issue in NHS primary dental care 30 …”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, it may only truly be successful if recording the MDS‐TDI defined outcomes act as a driver for payment. A lack of sufficient financial remuneration associated with the long‐term management of dental trauma was the main barrier for dentists to manage TDI in primary care 29 . This has long been identified as an issue in NHS primary dental care 30 …”
Section: Discussionmentioning
confidence: 99%
“…La comunicación y la colaboración entre estos profesionales son esenciales para garantizar un tratamiento integral y eficaz de las lesiones traumáticas faciales. (22) Las lesiones traumáticas de la boca y la cara pueden ser desafiantes debido a la complejidad anatómica y la importancia de preservar la función y la estética. Un enfoque estructurado y un manejo adecuado de las lesiones traumáticas de la boca y la cara son fundamentales para lograr resultados óptimos y prevenir complicaciones a largo plazo.…”
Section: Coordinación Interdisciplinariaunclassified
“…2 A recent questionnaire revealed that the majority of General Dental Practitioners (GDPs) had not managed an intrusion, extrusion or avulsion in the last year. 3 While GDPs feel confident in managing simple dental trauma, such as uncomplicated and complicated crown fractures, they are less confident in managing complex dental trauma. 3 The infrequent and unpredictable presentation combined with a lack of confidence and a distressed patient, results in an emotive situation and can be a significant cause of stress for the dental team.…”
Section: Introductionmentioning
confidence: 99%
“…3 While GDPs feel confident in managing simple dental trauma, such as uncomplicated and complicated crown fractures, they are less confident in managing complex dental trauma. 3 The infrequent and unpredictable presentation combined with a lack of confidence and a distressed patient, results in an emotive situation and can be a significant cause of stress for the dental team. Unfortunately, excessive stress has been shown to compromise operative performance as well as having a negative impact on non-technical skills, such as communication and decision making.…”
Section: Introductionmentioning
confidence: 99%